Potential of Novel EPO Derivatives in Limb Ischemia. (15th January 2012) - Joshi, Dhiraj; Tsui, Janice; Yu, Rebekah; Shiwen, Xu; Selvakumar, Sadasivam; Abraham, David J.; Baker, Daryll M.
Abstract : Erythropoietin (EPO) has tissue-protective properties, but it increases the risk of thromboembolism by raising the haemoglobin concentration. New generation of EPO derivatives is tissue protective without the haematopoietic side effects. Preclinical studies have demonstrated their effectiveness and safety. This paper summarizes the development in EPO derivatives with emphasis on their potential use in critical limb ischaemia.